2022
DOI: 10.1186/s12885-022-09378-7
|View full text |Cite
|
Sign up to set email alerts
|

Routes of administration, reasons for use, and approved indications of medical cannabis in oncology: a scoping review

Abstract: Introduction Some patients diagnosed with cancer use medical cannabis to self-manage undesirable symptoms, including nausea and pain. To improve patient safety and oncological care quality, the routes of administration for use of medical cannabis, patients’ reasons, and prescribed indications must be better understood. Methods Based on the Joanna Briggs Institute guidelines, a scoping review was conducted to map the current evidence regarding the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 136 publications
(150 reference statements)
0
10
0
Order By: Relevance
“…This dose dependency could also be affected by various forms of medical marijuana administration. Vinette et al discussed the importance of tracking the multiple routes of administration for future studies because of the lack of information in the current literature [ 12 ]. Although medical marijuana dosage is not quantified through research, we found that optimal medical marijuana of 470 mg per product was beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…This dose dependency could also be affected by various forms of medical marijuana administration. Vinette et al discussed the importance of tracking the multiple routes of administration for future studies because of the lack of information in the current literature [ 12 ]. Although medical marijuana dosage is not quantified through research, we found that optimal medical marijuana of 470 mg per product was beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Interest in the use of CBD to treat cancer is currently high among researchers and clinicians, as indicated by the large number of recently published articles. Several recent reviews of the topic have examined relevant aspects, including the biochemical, pharmacological, and molecular mechanisms of CBD activity in cells [ 4 , 23 ]; CBD’s mechanism-of-action in cell and mouse models of cancer treatment [ 105 , 106 ]; and its clinical use to manage cancer symptoms [ 107 , 108 ]. We have aimed to synthesize this information and identify unmet needs in the field (standard dosing and true randomization, comparison between pure CBD and CBD+THC formulations, and impact of drug combinations on CBD efficacy), which could serve as the focus for future research and, thus, hasten the clinical translation of CBD.…”
Section: Discussionmentioning
confidence: 99%
“…These manifestations can arise from disease progression and the adverse effects of antitumor treatments. [4][5][6][7] In response, patients have increasingly turned to cannabis-derived products to alleviate these symptoms, thereby enhancing their quality of life and facilitating adherence to cancer treatments. 2,6 Notably, cannabinoids prove especially valuable in clinical practice for patients unresponsive to conventional treatments.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] In response, patients have increasingly turned to cannabis-derived products to alleviate these symptoms, thereby enhancing their quality of life and facilitating adherence to cancer treatments. 2,6 Notably, cannabinoids prove especially valuable in clinical practice for patients unresponsive to conventional treatments. 8 Both preclinical and clinical studies have underscored the efficacy of natural and synthetic cannabinoids in managing symptoms such as nausea and vomiting, surpassing the effect of domperidone.…”
Section: Introductionmentioning
confidence: 99%